The new left and the origins of the Cold War - Maddox, Robert James (Princeton legacy library., 1974)
As more and more people are questioning the assumptions of present U.S. foreign policy they are reexamining the roots of these policies in the diplomacy of the Cold War. This scrutiny has made the origins of the Cold War the most controversial issue in American diplomatic history. Now a complete new dimension has been added to the debate by the charges leveled by Robert James Maddox in The New Left and the Origins of the Cold War. How did the Cold War begin? Who or what was responsible? Could it have been avoided? Was it a temporary condition created by a combination of individual personalit.